Environmental Impact of Massive Food Services and Homemade Meals: A Case Study on Stewed Chickpeas - Natalia Velastín; Rodrigo Contreras-Núñez; Ernesto Pino-Cortés; Lorena Espinoza Pérez; Fidel Vallejo; Andrea Espinoza Pérez (Applied Sciences)
The consequences of climate change directly affect food production and threaten food security. Therefore, efforts are needed to reduce environmental impacts while ensuring access to food. Massive food services play a key role in this context; however, related literature lacks comparative studies between home cooking and restaurants. Through life-cycle assessment, this research compares the environmental impacts generated by stewed chickpeas, a nutritious and flavorful meal prepared at a large food service offered by a public university, and those prepared at home using two recipes. The system boundaries consider the impact of ingredient production, processing, cooking, cooling, and reheating, as well as waste and wastewater generation. The functional unit (FU) weighs 100 g to facilitate comparison. The findings indicate that the recipe from the massive food service has a significant impact on human health, resulting in 3.54·10−7 DALY; meanwhile, the other two scenarios generate approximately 7.2·10−7 DALY. Moreover, regarding biodiversity impact, the recipe from the massive food service reaches 8.57·10−10 species.yr; by contrast, the other scenarios generate around 1.01·10−10 species.yr. Massive food services exhibit a lower environmental impact than home meals in preparing stewed chickpeas. This difference is primarily attributed to the cooling and reheating stages that occur when eating outside the home.